Enhanced Efficiency of Single and Tandem Organic Solar Cells Incorporating a Diketopyrrolopyrrole‐Based Low‐Bandgap Polymer by Utilizing Combined ZnO/Polyelectrolyte Electron‐Transport Layers. (12th July 2013) - Jo, Jang; Pouliot, Jean‐Rémi; Wynands, David; Collins, Samuel D.; Kim, Jin Young; Nguyen, Thanh Luan; Woo, Han Young; Sun, Yanming; Leclerc, Mario; Heeger, Alan J.
<x xml:space="preserve">Abstract</x> Power conversion efficiency up to 8.6% is achieved for a solution‐processed tandem solar cell based on a diketopyrrolopyrrole‐containing polymer as the low‐bandgap material after using a thin polyelectrolyte layer to modify the electron‐transport ZnO layers, indicating that interfacial engineering is a useful approach to further enhancing the efficiency of tandem organic solar cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>